2011
DOI: 10.1007/s10578-011-0229-2
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and Late Adolescent Emotional Adjustment: Mediating Effects of Discipline and Gender

Abstract: Research suggests that parenting styles are related to the types of discipline parents utilize and that the coupling of parenting styles and discipline techniques are related to child outcomes. Although extant research examines the effects of parenting styles and discipline on child and early adolescent adjustment, less is known about adjustment in late adolescents, also described as emerging adults. Thus, the current study investigated the relationships among parenting styles (e.g., authoritative, authoritari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 37 publications
4
49
1
5
Order By: Relevance
“…Moreover, McKinney, Milone andRenk (2011) andMilevsky, Schlechter, Netter andKeehn (2007) report that a democratic parenting style, generally characterized by a high level of emotional support and adequate control (Baumrind, 1991(Baumrind, , 1996, is associated with higher self-esteem among adolescents and young adults. Martinez and Garcìa (2007) found that adolescents with authoritarian parents (high demandingness and low responsiveness) exhibit the lowest scores for self-esteem.…”
Section: Self-esteem and Parentingmentioning
confidence: 99%
“…Moreover, McKinney, Milone andRenk (2011) andMilevsky, Schlechter, Netter andKeehn (2007) report that a democratic parenting style, generally characterized by a high level of emotional support and adequate control (Baumrind, 1991(Baumrind, , 1996, is associated with higher self-esteem among adolescents and young adults. Martinez and Garcìa (2007) found that adolescents with authoritarian parents (high demandingness and low responsiveness) exhibit the lowest scores for self-esteem.…”
Section: Self-esteem and Parentingmentioning
confidence: 99%
“…While similar pathways between other parenting factors and IS have been observed in both boys and girls [55], we found similar associations between parent relationships, self-esteem and IS in girls only. It could be that parent-child engagement does not affect boys’ self-esteem or emotional adjustment in the same way as girls, particularly when accounting for parental discipline [56]. …”
Section: Discussionmentioning
confidence: 99%
“…Además es importante considerar el efecto diferencial que se produce en la relación entre los padres y las madres con sus hijos, y los efectos que traen en el bienestar y resiliencia de los adolescentes, tal como se apreció en esta investigación. Este efecto diferencial ha sido igualmente reportado en otras investigaciones (Desjardins y Leadbeater, 2011;Mckinney, Milone, y Renk, 2011;Simons y Conger, 2007), donde los efectos de moderación/mediación del apoyo o relación con el padre y la madre son distintos.…”
Section: Discussionunclassified